Electromagnetic Field Analysis on Asymmetrical Three Phase Transformer - Arief Budi Ksatria; I Made Yulistya Negara; Dimas Anton Asfani; I Gusti Ngurah Satriyadi Hernanda; Daniar Fahmi; Muhammad Sulthon Novera Rega (JAREE (Journal on Advanced Research in Electrical Engineering), 2019)
This study deals with the effect of core lamination thickness on asymmetrical three-phase transformer to hysteresis curve. The asymmetrical three-phase transformer is a transformer that has different leg-length. The used transformer in this research has 5-kVA rating, and E-I core-cutting topology, and a larger leg size on center compared to the the side-legs of the transformer. Research on the effect of transformer core lamination thickness was done using finite-element method (FEM) to find out the magnetic field density (B) distribution and magnetic field intensity (H) at some points which the flux distribution flows. Variables of thicknesses used in the study were either intact or non-laminated-core transformer, 2.5 cm-laminated transformer core, and 0.03 cm-laminated transformer core. Each transformer has 39 monitor points to obtain the maximum value of B and H. Based on the simulation results, the highest magnetic field density value is in the transformer with 0.03 cm-laminated core, which is 2.174 Vs/m2 and the magnetic field density with the highest absolute average is in a transformer with a non-laminated-core, which is 1.837 Vs/m2. At the branching point of the core-cutting of the transformer with 0.03 cm-laminated transformer core have the highest magnetic field intensity value compared to the non-laminated-core transformer and 2.5 cm-laminated.Keywords: asymetrical leg, electromagnetic field, finite element method, hysteresis curve, three phase transformer.